Giant hepatic polycystosis. - Perrier, José P; Chevalier, Nelma; Bowley, Hilmer; Trostchansky, José (Cirugía del Uruguay, 1985)
Multiple cysts in the liver whether being or not being a par! of the polycystic disease, may be manifestad, among other symptoms, by hepatomegaly and compression sorrounding viscera. A clinical case is presented with a giant 7 litres protuding cyst affecting the urínary trae! with hydronephrosis and hematuria.